Some new recordeds of macrofungi from the Ngoc Linh mountain, Quang Nam province, Vietnam - Phu, Tran Thi; Kiet, Trinh Tam (Academia Journal of Biology, 2019)
Among 276 species of class Agaricomycetes isolated from the Ngoc Linh mountain, Quang Nam Province, we identified and recorded eight new species of macrofungi in Vietnam, namely Cymatoderma caperatum, Amanita xanthogala, Chlorophllum brunneum, Chlorophyllum hortense, Hymenopellis megalospora, Psathyrella longipes, Russula cystidiosa, and Serpula lacrymans. The morphologies, anatomical characteristics as well as applications of these species were demonstrated. Among these 8 newly recorded species in Vietnam, 2 species are edible mushrooms and 3 another species may be poisonous mushrooms.